Self-healable and pH-responsive spermidine/ferrous ion complexed hydrogel Co-loaded with CA inhibitor and glucose oxidase for combined cancer immunotherapy through triple ferroptosis mechanism - Tianqi Nie; Yifei Fang; Ruhe Zhang; Yishui Cai; Xiaobo Wang; Yuenong Jiao; Jun Wu (Bioactive Materials)
Tumor microenvironment governs various therapeutic tolerability of cancer such as ferroptosis and immunotherapy through rewiring tumor metabolic reprogramming like Warburg metabolism. Highly expressed carbonic anhydrases (CA) in tumor that maintaining the delicate metabolic homeostasis is thus the most potential target to be modulated to resolve the therapeutic tolerability. Hence, in this article, a self-healable and pH-responsive spermidine/ferrous ion hydrogel loaded with CA inhibitor (acetazolamide, ACZ) and glucose oxidase (ACZ/GOx@SPM-HA Gel) was fabricated through the Schiff-base reaction between spermidine-dextran and oxidized hyaluronic acid, along with ferrous coordination. Investigation on cancer cell lines (MOC-1) demonstrated ACZ/GOx@SPM-HA Gel may induce cellular oxidative stress and mitochondrial dysfunction through disrupting the cellular homeostasis. Moreover, with the facilitation of autophagy induced by spermidine, ACZ/GOx@SPM-HA Gel may trigger a positive feedback loop to maximally amplify cellular ferroptosis and promote DAMPs release. The anti-tumor evaluation on xenograft mice models furtherly proved the local injection of such hydrogel formulation could efficiently inhibit the tumor growth and distinctively promote the immunogenicity of tumor bed to provide a more favorable environment for immunotherapy. Overall, ACZ/GOx@SPM-HA Gel, with such feasible physiochemical properties and great biocompatibility, holds great potential in treating solid tumors with acidosis-mediated immunotherapy tolerance.